Hamlet's problematic revenge : forging a royal mandate - Zak, William F., 1945- (Lexington Books, 2015)
Amidst a wealth of previously unremarked figurative mirrorings, as well as much of the seemingly digressive material in Hamlet within Shakespearean studies, Hamlet's Problematic Revenge brings to light a new interpretation of the tragic problem in the play.